ELASTIC CONDUCTIVITY OF SILICENE AND GERMANENE NANORIBBONS - Lebedeva Olga; Lebedev Nikolay; Lyapkosova Irina (St. Petersburg Polytechnical University Journal: Physics and Mathematics, 2019)
The results of a theoretical study of the piezoresistive properties of ideal silicene and germanene nanoribbons with different types of conductivity are presented. Within the framework of the Hubbard model, the band structure of the studied nanoparticles is simulated and the longitudinal component of the elastoconductivity tensor is analytically calculated, and its dependence on the relative strain of longitudinal compression and tension and the width of the nanoribbon is studied.